2010
DOI: 10.1007/s11199-010-9874-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender in Spanish Daily Newspapers

Abstract: The purpose of this study was to examine the portrayal of women and men in a Spanish daily newspaper and to find whether there were gender differences among the authors of the articles in said newspaper. A content analysis was conducted of 4,060 articles and advertisements from 24 issues of a randomly selected, large-circulation, Spanish newspaper. Men were found to be more commonly featured in the articles, photographs, and advertisements than women, and they would usually be soldiers, athletes or high-rank b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 63 publications
5
20
0
5
Order By: Relevance
“…The under-representation of women in the media has been found in studies conducted in Spain and other countries (Cf. Calvo and Gutiérrez, 2016;Collins, 2011;Mateos de Cabo, Gimeno, Martínez and López, 2014;Matud et al, 2011;Stanley, 2012;WACC, 2015). It has also been confirmed that, similar to what these studies found, the representation of women and men is informed by gender stereotypes that attribute the power and authority to men.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The under-representation of women in the media has been found in studies conducted in Spain and other countries (Cf. Calvo and Gutiérrez, 2016;Collins, 2011;Mateos de Cabo, Gimeno, Martínez and López, 2014;Matud et al, 2011;Stanley, 2012;WACC, 2015). It has also been confirmed that, similar to what these studies found, the representation of women and men is informed by gender stereotypes that attribute the power and authority to men.…”
Section: Discussionmentioning
confidence: 99%
“…Coding was performed based on the system developed by Matud et al (2011) for the analysis of newspaper contents, as it has shown high reliability levels. These codes have been reviewed and some of their categories have expanded to collect all the information.…”
Section: Coding Procedures and Content Analysis Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Los resultados relativos a la mayor representación de los hombres frente a las mujeres tanto en la parcela informativa de los medios de comunicación como en la publicidad coinciden con los de otros estudios españoles (cfrs., Crolley y Teso, 2007;Fagoaga y Secanella, 1984;Gallego, Altés, Melús, Soriano y Canton, 2002;Matud, Rodríguez y Espinosa, 2011;Rodríguez et al, 2008) y con los realizados en otros entornos geográficos y culturales (véase, por ejemplo, Collins, 2011;Jolliffe, 1998;Len-Ríos et al, 2005).…”
Section: El Porcentaje De Mujeres Y Hombres Como Figuras Centrales Deunclassified